IDEOLOGI FEMINISME PADA HIKAYAT MINANGKABAU - Tiara Noviarini (Sekolah Tinggi Pariwisata Mataram, 2021)
This research aims to describe the role of Minang women in the Minangkabau Saga of KabaCindua Mato and Novel of MemangJodoh and to depict the comparison of Minang women in those two works with the traditional Minangkabau cultural values. This research wasa qualitative study with a content analysis method. The approach of this research was comparative literature with an interdisciplinary perspective. The results of this study are as follows (1) Minang women in the KabaCindua Matoare represented by ancient Minang women who are identical to adherence to customs and understand their position as Minangwomen. In the Novel of MemangJodoh, the depiction of Minangwomen focuses more on cases or unfair treatment because of the thoughts of the society or leaders of certain people who do not lead to customs that they should be referred to. (2) The comparison of Minang women in the Saga of KabaCindua Mato and the Novel of MemangJodoh with Minangkabau culture has providedan important note. It is that Minangwomen have several clear positions both as unmarried and married persons.